Study of Some Physiological and Histological Parameters of Albino Rats Administrated with a Herbal Obesity Slimmer Product - Ikhlass A. Al-Hilaly; Meison Abdulbary; Sadeq Jaffer AlZubaidi; Ibraheem Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The modern studies on the treatment of obesity have dedicated on the potential activity of plants to control obesity on the metabolism of lipid and glucose. The aim of this study is to investigate about the effect of AB slim on body metabolism of its – takers and determine its safety. 16 female rats (150 - 250) divided equally into 4 groups, the first group considered as control group and administered distilled water, the three other groups daily administered the prepared aqueous solution of AB slim capsule for 45 days. The animals weighed after 24 hr. of the last administration, the animals were weighed. The results showed after weeks of treatment that the animals gain weight instead of losing it and there were no beneficial effects of this remedy on lipid profile, in contrast there was an increase in LDL levels and decrease in HDL. The hisopathological study showed degeneration and necrosis in most organs , liver, kidney, spleen and gastrointestinal tract.